Dermatogliphic distinctness of the Hel Kashubians - Liczbińska, Grażyna (Anthropological Review, 1997)
The study consisted in the qualitative and quantitative analysis of epidermal ridges on fingers of the Kashubians from the Hel Peninsula and those from Pomerania. On the basis of the obtained data similarities and differences between the Kashubians and other Poles with regard to these traits were assessed.